2015
DOI: 10.1371/journal.pone.0142901
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 Promotes Mitochondrial Dysfunction–Triggered Striatal Neurodegeneration via Autophagy and Apoptosis Activation

Abstract: Impairments in mitochondrial energy metabolism are thought to be involved in many neurodegenerative diseases. The mitochondrial inhibitor 3-nitropropionic acid (3-NP) induces striatal pathology mimicking neurodegeneration in vivo. Previous studies showed that 3-NP also triggered autophagy activation and apoptosis. In this study, we focused on the high-mobility group box 1 (HMGB1) protein, which is important in oxidative stress signaling as well as in autophagy and apoptosis, to explore whether the mechanisms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Nevertheless, overexpression of Beclin1 could instead restore autophagy, promote α-synuclein clearance (Song et al, 2014 ) and ultimately break the vicious cycle shown in Figure 7 . Moreover, HMGB1 inhibitor glycyrrhizin pretreatment or HMGB1 knockdown had also been proven to facilitate the autophagy flux and rescue 3-nitropropionic acid induced striatal damage (Qi et al, 2015 ), which is precisely consistent with the study results. In conclusion, this study has identified that HMGB1 have a higher affinity for Beclin1 and thereby perturb the Beclin1-Vps34 complex formation, thus resulting in subsequent autophagy dysfunction and α-synuclein accumulation.…”
Section: Discussionsupporting
confidence: 88%
“…Nevertheless, overexpression of Beclin1 could instead restore autophagy, promote α-synuclein clearance (Song et al, 2014 ) and ultimately break the vicious cycle shown in Figure 7 . Moreover, HMGB1 inhibitor glycyrrhizin pretreatment or HMGB1 knockdown had also been proven to facilitate the autophagy flux and rescue 3-nitropropionic acid induced striatal damage (Qi et al, 2015 ), which is precisely consistent with the study results. In conclusion, this study has identified that HMGB1 have a higher affinity for Beclin1 and thereby perturb the Beclin1-Vps34 complex formation, thus resulting in subsequent autophagy dysfunction and α-synuclein accumulation.…”
Section: Discussionsupporting
confidence: 88%
“…HMGB1 is important for oxidative stress response and cell death signaling. HMGB1 has been shown to play an important role in signaling for mitochondrial dysfunction‐induced apoptosis . Ding et al reported that the HMGB1 together with its receptor Toll‐like receptor 4 plays a significant role in the pathogenesis of ischemic‐reperfusion injury and can induce apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…The high mobility group box 1 protein is a chromatin binding protein that recognizes DNA damage and promotes binding to p53 to stimulate an oxidative stress response, namely, autophagy or apoptosis. Studies investigating the correlation of HMGB-1 and mitochondrial dysfunction in 3-nitropropionic acid treated animals have been conducted to study the role HGMB-1 may have on striatal neurodegeneration in vivo and in vitro [ 545 ]. They demonstrated that HMGB-1 binds to beclin-1 to regulate autophagy, thereby establishing a new mechanism to study in striatal neurodegeneration via autophagy and apoptosis.…”
Section: An Overview Of Some Neurodegenerative Diseasesmentioning
confidence: 99%